Metal-interacted histidine dimer: an ETS-NOCV and XANES study. Issue 45 (19th April 2016) - Umadevi, P.; Senthilkumar, L.
Abstract : We have analyzed the metal coordination in a histidine dimer, hydrated with a water molecule, based on the extended transition state scheme with the theory of natural orbitals for chemical valence (ETS-NOCV). Abstract : We have analyzed the metal coordination in a histidine dimer, hydrated with a water molecule, based on the extended transition state scheme with the theory of natural orbitals for chemical valence (ETS-NOCV). Metal interaction weakens and strengthens the CO and C–N bonds respectively, which indicates σ bond formation between the metal and the ligand. Frequency analysis reveals CO bond exhibits a red shift, which confirms that the π-back donation of electrons takes place through this bond. From the ETS-NOCV analysis, the electrostatic term is dominant over the orbital term. NOCV analysis indicates that the switching of bond strength between C–N bond and CO bond in neutral and zwitterionic systems respectively is due to the amount of back donation in TM 2+ –N and TM 2+ –O bonds (TM 2+ = Cu, Zn, Ca, Mg). K-edge XANES spectra for the metal indicates that oxidation state of Zn and Ca increases while for Cu and Mg it decreases. Oxygen K-edge spectra indicate that metals like zinc and copper back-donate the electrons largely to ligands.